Pepper power: short-term impact of pepper consumption on the gut bacteriome composition in healthy volunteers - Owolo,Oluwafayoke; Audu,Haruna J.; Afolayan,Ayorinde O.; Ayeni,Funmilola A. (PeerJ, 2024)
Background Pepper from Capsicum species is a well-established spice with a rich history of culinary use. Some observations have linked its consumption to gastrointestinal discomfort and alterations in stool patterns while it is considered beneficial in some cultures. However, there is lack of information on the direct effect of pepper consumption on human gut microbiota, we conducted dietary intervention studies to assess the impact of pepper on gut bacteriome composition in humans. Methods Ten healthy volunteers were recruited, and each person received 200 ml of 0.14 g/ml fresh Habanero Pepper (Capsicum chinense) daily over a 4-day period after which they abstained from pepper consumption for the subsequent 4 days before resumption of their normal diet. Stool samples were collected at baseline, after pepper consumption, after 4 days without pepper and after 4- and 6-days resumption of normal diet. We sequenced the V3-V4 region of the 16S rRNA gene and analyzed microbial diversity and composition using the QIIME2 pipeline and relevant R packages. Results Consumption of pepper over a 4-day period led to a higher abundance of Verrucomicrobia, a phylum rarely found in significant proportions at other time points. There was a gradual depletion of Shigella and Staphylococcus spp. from baseline untill the end of the study. Other taxa showed timepoint specific associations, emphasizing the potential impact of short-term dietary interventions on the relative abundance of these genera. Conclusions Our study adds nuance to the understanding of diet-microbiota interactions, highlighting the intricate relationship between pepper consumption and gut bacteriome composition. Further exploration of these dynamics holds promise for personalized dietary recommendations and targeted interventions to support gut microbial health.
Keywords: Pepper; 16S sequencing; Capsicum chinense; Gut microbiota